Customary Land Tenure Practices and the Livelihoods of Peasants in the Nanumba Traditional Area - Laarbik, Y. (University Of Ghana, 2017)
It is mind bothering if few people inhabiting a vast area of a region should have issues with livelihoods due to access to land. Livelihoods of people in the three northern regions of Ghana depend largely on the availability and ease of access to land. On the other hand land in the Nanumba traditional area is under the allodial hold of the overlord and overseen by the sub and divisional chiefs. The indigenes within the royal families are entitled to usufruct rights in the communally held land. The customary practices of farmland allocation, determination of interests and rules of engagement in land deals possibly leave behind issues of discrimination, inequality and deprivation with livelihoods consequences. This study adopted a case study design and mixed methods of data collection with questionnaire, FGDs and in-depth interviews as instruments of data collection. It gathered both qualitative and quantitative data on modes of land allocation, gendered issues in land allocation, access to farmland and livelihood outcomes, and the state of food security. Descriptive techniques like frequency and tabulations were adopted to analyse the data. It therefore observed that access to farmland was predominantly through free gifts and inheritance, with incidence of land sales around urbanizing areas like Bimbilla sub-traditional area. The inequality, discrimination and exclusions in gendered land access were socially constructed. It also observed low income earnings with widespread household food insecurity across the study sites. The study observed that peasants borrowed food stuff and also sold labour predominantly as mitigation measures. It therefore recommended participatory stakeholder interventions involving the chiefs, gender desk officers, local NGOs and the local government in formulating effective agrarian land reforms to enhance real access to farmland, especially by females in the area; while taking steps to diversify livelihoods of households in the traditional area.
Thesis (MPhil.)
Keywords: Land Tenure; Livelihoods; Peasants; Ghana